Translation, cross-cultural adaptation and validation of the universal Welch Emotional Connection Screen using primary and bilingual Spanish-speaking coders of videotaped mother-child interactions - Amie A. Hane; Robert J. Ludwig; Amy G. Martinez; Cynthia Masese; Ulla Vanhatalo; Cliff Goddard; Marc E. Jaffe; Michael M. Myers; Michael M. Myers; Michael M. Myers; Martha G. Welch; Martha G. Welch; et al. (Frontiers Media S.A., 2024)
IntroductionUsing clear explicit translatable language, we translated the Welch Emotional Connection Screen into a new universal language instrument, the English uWECS. In this study, we had two aims: Aim 1 was to establish concurrent validity of the uWECS by comparing scores coded by primary Spanish-speaking coders using the Spanish translation of the uWECS to scores coded by bilingual, secondary Spanish-speaking coders using the oWECS. Aim 2 was to establish the criterion-related validity in terms of oWECS and uWECS performance in tracking change in autonomic emotional connection (AEC) during the course of an intervention among preschool aged children.MethodsWe created a library of 52 five-minute Spanish-speaking mother-child videos that were collected during a randomized controlled trial of Mother-Child Emotional Preparation intervention (MCEP). The videos were collected at two time points, at enrollment and at a 6-month follow-up. The subsample of Primary Spanish-Speaking dyads from the MCEP study were coded by two independent teams of coders. We trained primary English-speaking (bilingual Spanish) coders on the oWECS, using the original training program. A different team of primary Spanish-speaking coders coded the same cases using the novel uWECS guide and trained briefly for reliability with the Spanish uWECS translation materials.ResultsWe found that the Spanish oWECS and Spanish uWECS ratings from the baseline and 6-month follow-up observations were robustly correlated, with intraclass correlations ranging from .81 to .84 and all p-values<.001, thus demonstrating sound concurrent validity for the uWECS. The oWECS and uWECS scores also achieved parallel results when evaluating the efficacy of the MCEP for primary Spanish-speaking dyads. Both the AEC scores of the oWECS [F(1, 27) = 4.31, p < .05] and the scores of the uWECS [F(1,27) = 4.06, p < .05] similarly demonstrated significant change post intervention, thus demonstrating sound criterion-related validity of the uWECS.DiscussionThese findings demonstrate that the uWECS can be used to measure parent/child AEC in linguistically diverse populations and cultures.